JENNIFER EGAN’S “A VISION FROM THE GOOD SQUAD”: A NARRATIVE OF HEALTH, DISEASE, AND DEATH - Mihaela MUDURE (Studia Universitatis Babeş-Bolyai. Philologia, 2019)
Jennifer Egan’s A Vision from the Good Squad: A Narrative of Health, Disease and Death. This paper analyzes Jennifer Egan’s novel/ short story cycle entitled A Visit from the Goon Squad, winner of the 2011 Pulitzer Prize for fiction. The chapters/stories shift back and forth in time, moving from the late sixties to the present day and into the near future. The Proustian influence is obvious in this fascinating narrative of the self, the ailing body, and finally death. The interesting structure of the book, due to the influence of the TV series and the power point slides, adds a fascinating quality to this text which is the result of a vision that has all the characteristics of the contemporary age.